Advances in economic theory fifth World congress - Bewley, Truman F (ed.) (Cambridge, 1989)
The Econometric Society holds a World Congress every five years. The program of these congresses has traditionally included a series of invited symposia, where speakers survey important recent advances in economic theory and econometrics. This volume, with its focus on economic theory and its companion volumes on econometrics contain papers delivered at the Fifth World Congress held in 1985. Designed to make material accessible to a general audience of economists, these articles should be helpful to anyone with training in economics, who wishes to review past ideas and tendencies in the subject.
Keywords: Economics